The Relationship Between Work Motivation and Performance of Members of Ganto Campus Newspaper, University Of Padang - Nur, Rizka Mutiah; Solfema, Solfema (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by the poor performance of members of the Ganto Campus Newspaper, Padang State University, which was allegedly due to the low work motivation of members of the Ganto Campus Newspaper, Padang State University. This study aims to describe the work motivation of members of the Ganto Campus Newspaper, Padang State University and the performance of members of the Ganto Campus Newspaper, Padang State University and to determine the relationship between work motivation and the performance of members of the Ganto Campus Newspaper, Padang State University. This study uses a quantitative approach with a correlational type. The population of this study was members of the Ganto Campus Newspaper, Padang State University in the 2022 management year, totaling 32 people and 70% of the sample was taken, namely 22 people, using a stratified random sampling technique. Data collection techniques using questionnaires and data analysis techniques using percentage formulas and product moment formulas. The results showed that the work motivation of members of the Ganto Campus Newspaper, Padang State University was low, the performance of members of the Ganto Campus Newspaper, Padang State University was classified as poor, and there was a significant relationship between work motivation and the performance of members of the Ganto Campus Newspaper, Padang State University.